Open for investment: Novel nature for peace project in Colombia - Villarino, Ma Eliza J (2024)
A project promoting biodiversity conservation, climate mitigation and peacebuilding in Colombia which the Alliance of Bioversity International and CIAT has supported in structuring is now eligible for funding under one of the government’s tax credit programs targeting conflict-affected areas.